Nero: A Deterministic Leaderless Consensus Algorithm for DAG-Based Cryptocurrencies - Morais, Rui; Crocker, Paul; LEITHARDT, VALDERI (My University, 2023)
This paper presents the research undertaken with the goal of designing a consensus algorithm for cryptocurrencies with less latency than the current state-of-the-art while maintaining a level of throughput and scalability sufficient for real-world payments. The result is Nero, a new deterministic leaderless byzantine consensus algorithm in the partially synchronous model that is especially suited for Directed Acyclic Graph (DAG)-based cryptocurrencies. In fact, Nero has a communication complexity of O(n3) and terminates in two message delays in the good case (when there is synchrony). The algorithm is shown to be correct, and we also show that it can provide eventual order. Finally, some performance results are given based on a proof of concept implementation in the Rust language.
Keywords: consensus; byzantine; directed acyclic graph